Evaluating the quality of high school coursebooks: Implications for materials development - Sukarno, Sukarno; Jinabe, Megan; Gharamah, Fadhl Mohammed Awadh (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
A coursebook is one of the essential learning resources. However, limited research has highlighted the evaluation of English coursebooks for the high school level. This research intends to assess the efficacy of three high school English coursebooks under the Merdeka Curriculum to determine their strengths and weaknesses in meeting curriculum expectations and enhancing student learning. While the coursebooks are designed to aid English teaching and integrate reform, many reports have emerged regarding their usability, content relevance, and alignment with the local context. In evaluating these coursebooks with SQRAR, this research aims to analyze the suitability of these materials for the target students, the variety of exercises proposed, and the balance achieved between theoretical instruction and practical language use. The findings highlight the challenges educators and learners face regarding these materials and articulate suggestions for future coursebook revisions, such as adding more explicit teaching strategies, giving greater attention to pluralistic approaches, increasing engagement with authentic materials, and more modern technology-oriented tasks. The evaluation seeks to support ongoing efforts in developing curricula to ensure that English coursebooks can effectively foster students' learning.